Industry growth patterns: a closer look at output, productivity, and hours worked from 1990 to 2024. - Modica, Nathan (Monthly Labor Review, 2025)
The article analyzes industry growth patterns in the United States from 1990 to 2024, focusing on output growth driven by productivity, hours worked, or a balance of both. It highlights that while overall growth in hours worked has slowed since 2000, many industries have achieved significant output growth primarily through productivity gains, with notable examples including commercial equipment wholesalers and software publishers. Conversely, the restaurant industry has experienced hours-driven growth, although recent trends indicate a shift towards productivity growth post-2019. The article emphasizes the diverse responses of different industries to economic changes and technological advancements, providing a nuanced understanding of output growth in the context of labor market dynamics.